2023
DOI: 10.1186/s12245-023-00504-1
|View full text |Cite
|
Sign up to set email alerts
|

Classification of suicidal behavior calls in emergency medical services: a systematic review

Abstract: Background The aim of this systematic review was to examine the classification of calls for suicidal behavior in emergency medical services (EMS). Methods A search strategy was carried out in four electronic databases on calls for suicidal behavior in EMS published between 2010 and 2020 in Spanish and English. The outcome variables analyzed were the moment of call classification, the professional assigning the classification, the type of classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(285 reference statements)
0
2
0
Order By: Relevance
“…Following on from this reflection, Anderson et al ( 40 ) state that little training is available on how visits for suicidal behavior should be documented and that research that relies on international disease classification codes included in medical records to study suicide sometimes significantly underestimates cases of suicide attempts and suicidal ideation. Furthermore, in a recently published systematic review, we concluded that each out-of-hospital emergency service uses a different classification, making it difficult to make valid and reliable comparisons of the data collected in these care settings ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following on from this reflection, Anderson et al ( 40 ) state that little training is available on how visits for suicidal behavior should be documented and that research that relies on international disease classification codes included in medical records to study suicide sometimes significantly underestimates cases of suicide attempts and suicidal ideation. Furthermore, in a recently published systematic review, we concluded that each out-of-hospital emergency service uses a different classification, making it difficult to make valid and reliable comparisons of the data collected in these care settings ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The most commonly used communication channel for this is typically the telephone, with specific numbers varying from one country to another. [3][4][5] In Thailand, the telephone number used for receiving reports of medical incidents is 1669, which operates around the clock, covering all areas of Thailand. 6 It's worth noting that previous studies 7,8 have demonstrated that achieving shorter response times positively impacts the evaluation of symptoms, diagnosis, and treatment procedures, especially in cases of time-sensitive medical conditions.…”
Section: Introductionmentioning
confidence: 99%